Angle specific analysis of hamstrings and quadriceps isolinetic torque identify residual deficits in soccer players following ACL reconstruction: a longitudinal investigation - Read, P. J.; Trama, R.; Racinais, S.; McAuliffe, S.; Klauznicer, J.; Alhammoud, M. (Journal of Sports Sciences, 2022)
Analysing the isokinetic curve is important following ACL reconstruction as there may be deficits in torque production at specific points throughout the range of motion. We examined isokinetic (60°.s-1) torque-angle characteristics in 27 male soccer players (24.5 ± 3.9 years) at 3 time-points (17 ± 5; 25 ± 6; and 34 ± 7 weeks post-surgery). Extracted data included knee flexor and extensor peak torque, conventional hamstrings: quadriceps (H/Q) ratio, and angle-specific torque using Statistical Parametric Mapping (SPM). There were significant involved limb increases in extension peak torque at each assessment (p<0.001); however, asymmetry favouring the un-involved limb was observed (p<0.01). Flexion peak torque was greater on the un-involved limb at assessments 1 and 2 only (p<0.05). The angle of peak torque was not significantly different at individual time-points or within-limbs across the 3 assessments. SPM revealed involved limb angle-specific reductions in extension torque across the full range of motion at time-points 1 and 2 (p<0.001) but only in angles [51-80°] at assessment 3 (p<0.05). Between limb H/Q angle differences [33-45°] were shown at assessments 2 and 3. The ratio ranged from 1.60-0.74 depending on the angle tested. Angle-specific moment curves are useful for monitoring patterns of strength development during rehabilitation.